Osmotic adjustment and up-regulation expression of stress-responsive genes in tomato induced by soil salinity resulted from nitrate fertilization - Chang, Tingting; Zhang, Yujie; Xu, Hui-lian; Shao, Xiaohou; Xu, Qicong; Li, Fenglan; Yu, Lina; Zhang, Zhanyu (International Journal of Agricultural and Biological Engineering, 2018)
Concerns about the soil salinity caused by excessive fertilization have prompted scientists to clarify the detailed mechanisms and find techniques to alleviate the damage caused by this kind of soil salinity. Aims of this study were to elucidate the effect of soil salinity caused by nitrate fertilization and the differences in salinity effect between nitrate salts and NaCl salt with analyses at various levels of crop physiology and molecular biology. A microbial inoculation was also tried to verify whether it could alleviate the salinity-induced loss and damages. In three experiments (Exp I, II and III), nitrate salts (NS) of Ca(NO3)2 and KNO3 were applied to potted tomato plants to simulate the soil salinity caused by fertilization and a microbial inoculant (MI) was applied. Photosynthesis was measured using Li-6400. Osmotic adjustment was analyzed using the mathematically modeled pressure-volume curve; O2- concentration and activity of SOD and nitrate reductase were measured. Expression of nitrate reductase gene and the stress-responsive gene DREB2 was analyzed using the real-time PCR method. In Exp I and II, where the applied NS amount was moderate, NS application at low concentration induced increases in O2- and MDA concentrations and plants acclimated to the soil salinity as the treatment prolonged for weeks. The acclimation was contributed by osmotic adjustment, activation of SOD and re-compartmentation of cell water between symplasm and apoplasm. These adjustments might be ultimately attributed to up-regulation of stress-responsive genes such as DREB2 as well as the nitrate reductase (NR) gene. However, in Exp III, applications of NaCl and NS at high concentration could not show positive effects as NS did. Application of MI synergistically increased the xerophytophysiological regulation caused by NS and alleviated the salinity damage in addition to its own positive effects on the tomato plants. Different from NaCl, nitrate salts at low application rate increased the total biomass and fruit yield of tomato and induced up-regulation expression of stress-responsive genes and the consequent active osmotic adjustment. However, nitrate application at high level negatively affected tomato plants irrespective of the gene up-regulations. Application of MI alleviated the salinity damage and synergistically increased the xerophytophysiological regulation caused by the soil salinity in addition to its positive effects on the tomato crop but the detailed mechanisms needed to be clarified in future further studies. Keywords: nitrate fertilizer, osmotic adjustment, salinity stress, soil salinization, tomato (Solanum lycopersicum); xerophytophysiology, microorganism, bioremediation DOI: 10.25165/j.ijabe.20181103.2952 Citation: Chang T T, Zhang Y J, Xu H L, Shao X H, Xu Q C, Li F L, et al. Osmotic adjustment and up-regulation expression of stress-responsive genes in tomato induced by soil salinity resulted from nitrate fertilization. Int J Agric & Biol Eng, 2018; 11(3): 126–136.